Column restraint in post-tensioned self-centering moment frames. - Chou, Chung-Che (Earthquake engineering & structural dynamics.)
Gaps between beam-to-column interfaces in a post-tensioned (PT) self-centering frame with more than one column are constrained by columns, which causes beam compression force different from the applied PT force. This study proposes an analytical method for evaluating column bending stiffness and beam compression force by modeling column deformation according to gap-openings at all stories. The predicted compression forces in the beams are validated by a cyclic analysis of a three-story PT frame and by cyclic tests of a full-scale, two-bay by first-story PT frame, which represents a substructure of the three-story PT frame. The proposed method shows that compared with the strand tensile force, the beam compression force is increased at the 1st story but is decreased at the 2nd and 3rd stories due to column deformation compatibility. The PT frame tests show that the proposed method reasonably predicts beam compression force and strand force and that the beam compression force is 2 and 60% larger than the strand force with respect to a minor restraint and a pin-supported boundary condition, respectively, at the tops of the columns. Therefore, the earlier method using a pin-supported boundary condition at upper story columns represents an upper bound of the effect and is shown to be overly conservative for cases where a structure responds primarily in its first mode. The proposed method allows for more accurate prediction of the column restraint effects for structures that respond in a pre-determined mode shape which is more typical of low and mid-rise structures.